Impact of home financing on liquidity risk in Malaysian banks - Abdo, Aiuob Ali Abdulqader (2019)
Liquidity risk in banks is a major issue following the 2008 Global Financial Crisis. Liquidity risk as one of the main risks faced by the bank and cannot be ignored anymore in the banks. liquidity risk refers to the inability of banks in meeting the due date obligation. The main objectives of this study to investigate the impact of home financing and other factors on the liquidity risk of Islamic and conventional banks in Malaysia. The total numbers of 12 Islamic and 12 conventional banks are used as sample of the study for the period of 2004-2018 to be regressed using Fixed Effect Model (FEM). The results of the study show that home financing has positive relationship with Islamic and commercial bank liquidity risk in Malaysia and bank size has negative and significant relation with the liquidity risk. Expense to net income has significant relationship with the conventional banks and it is insignificant for Islamic banks. For conventional banks only inflation has significant impact on the liquidity risk of Malaysian banks. The limitation of the study only considering home financing and selected Islamic and commercial banks in Malaysia. therefore, it is recommended, to consider studying other types of loan and all the Islamic and commercial banks in Malaysia. Future studies should also consider examining the impact of the two new ratios suggested by the Basel Committee on liquidity risk in Malaysian Islamic and commercial banks.